Trend 1994 - 1998. Statistics Canada. CANSIM: Health - Health Care Services | Country: Canada | Province: Newfoundland and Labrador | Table: Contact with dental professionals, by age group and sex, household population aged 12 and over | Variable: 12-14 years, Contact with dental professionals in past 12 months, Both sexes | Units: # Persons, 1994-1998. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-112. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: Health - Health Care Services | Country: Canada | Province: Newfoundland and Labrador | Table: Contact with dental professionals, by age group and sex, household population aged 12 and over | Variable: 12-14 years, Contact with dental professionals in past 12 months, Both sexes | Units: # Persons, 1994-1998. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-112. Dataset: Presents data on contact and experiences with the Canadian health care system including: doctors, dentists and other health professionals; access to health care; waiting times; patient satisfaction; unmet health care needs; barriers to accessing care; prescription drug use; residential care facilities; hospitalization; as well as use of alternative medicine and health services. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: Health and Vital Statistics Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Health Services, Health, Health Care Services Utilization, Health Care Access